The Influence of Law-and-Economics on the Ideological Center of Civil Society – The New American Formalism with a European Counterpoint - Sebastian Ciobotaru (Washington University Global Studies Law Review, 2019)
Law-and-economics has been the dominant methodology in United States’ adjudication and law commentary for nearly 35 years. Because of its efficiency-only approach, law-and-economics has transformed the law itself from the impartial anchor of our social system into a political tool that legitimizes a new “false center.” Consequently, by failing in its role as a neutral force immune to political bias, the practice of law as advocated by law-and-economics constantly aids the neoliberal counter-revolution to commodify most aspects of our lives and foster a generation of corporate consumers bereft of traditional notions of liberty and autonomy. The main drive behind this critique is the desirability of promoting a different type of legal discourse, one that would help ground society’s “true center.” As a useful counterpoint, the relatively peaceful and constant progression towards “true center” values in Europe is presented. This development has not been countered by a judicial method of analysis predisposed to conservative values. As such, Europeans are able to enact laws that are better adapted to modern human necessities and which carry the same Enlightenment promises of justice and equality on which the United States has been founded. Several reasons for the divergence between these two related western systems are discussed, underlining the irony of a nominally formalist European jurisprudence that is nevertheless enacting the core values of the American legal realist agenda, while the law-and-economics methodology, a purported descendent of the realists, is instituting a new limiting and conservative formalism in the United States. Ultimately, law in the United States needs to be brought back to the aspirational place the Founders had envisioned for it - it needs to be, once again, the balanced arbiter that grounds the “true center” of American society, and not yet another political tool.
Keywords: economics; civil society; formalism; europe; law